Front-matter - Windia, Wayan P. (Udayana Journal of Law and Culture, 2017)
We are very grateful to launch the first edition of Udayana Journal of Law and Culture. This new journal offers a distinctive legal insight as it makes links to culture. ‘Transforming Local Wisdom’ has been chosen as the central topic of this edition in order to give a wider space for writers to discover and reveal any values and wisdom that exist in various types of communities that may have impacts to the creation, implementation, and enforcement of law. This topic has also been expected to encourage authors to scrutinize, or even criticize any local practices that may not be regarded as wisdom for the reason of incompatibility with laws and regulations. The five articles published in this edition were selected from many articles that have been received by the editors. The first and second articles discuss the situation faced by indigenous people with regards to their constitutional and legal rights over the land and participation in economic activities. The first article discusses constitutional apllication and interpretation on the indigenous tenure lands that have been functionally and culturally occupied by Brazilian Natives while the second one talks about legal concept of sustainable tourism that is expected to empower the economic ability of indigenous people, both in Bali-Indonesia and Australia, to harness the advantages of tourism. A comparative study between Indonesia and Australia is not only discussed in the second article but also deliberated in the third article, focuses on the incorporation of local wisdom into the consumer protection legal regime and argues that such incorporation encourages the receptiveness of globalization and the convergence of consumer protection in Indonesia and Australia. The forth article discovers that wisdom has been construed in legal manner creating a distinct ASEAN human rights regime. In addition, it argues that local wisdom has been formalised in order to create a distinct sub regional human rights norms and mechanisms contextualising way of life of the Southeast Asian peoples. Human rights in Southeast Asian context in the forth article may be linked with fundamental rights in the global and European contexts, as discussed in fifth article. Beside elaborating the issue of fundamental rights, this essay also critically talks about the issue of local wisdom by arguing that the incorporation of local wisdom and philosophies that are traditional and typical for a limited group is in conflict with the idea that global justice requires the adoption of commonly accepted principles. We expect this edition will encourage academicians and practitioners all over the world to contribute their articles to the UJLC for the upcoming edition. Lastly, we would like express our great appreciation to all authors, submissioners, and Board of Editors who are scholars from universities in Indonesia, Australia, the Netherlands, and the United States of America, and also the editorial members for their kindly cooperation in the completion of the first UJLC edition.